Rough night [videorecording (DVD)] - Aniello, Lucia; Johansson, Scarlett, 1984-; McKinnon, Kate, 1984-; Kravitz, Zoë, 1988-; Moore, Demi; Bell, Jillian, 1984-; Glazer, Ilana; Burrell, Ty, 1967- (Sony Pictures Home Entertainment, 2017)
Five friends from college reunite when they rent a beach house in Miami for a wild bachelorette weekend that goes completely off the rails. Just when all hope is lost, they realize there's more to the story than they could've ever imagined.